O ensino de julgamento e tomada de decisão nos cursos de graduação em ciências contábeis no Brasil - Maia, Kallil Iangle Castro (2012)
The convergence of Brazilian accounting standards to international standards has enabled our rules changed to a new level. The previous accounting principles were based on a detailed set of rules and regulatory authorities checked the adequacy of the Financial Statements to these rules. With the change came a new paradigm, the new standards are based more on principles rather than rules, specifically in accordance with International Financial Reporting Standards (IFRS) in the preparation of Financial Statements, which relies on professional judgment on a larger scale than under the old rules-based standards. This work aims to investigate how the trial has been approached Judgment and Decision Making (J&DM) in Brazilians bachelor’s courses in Accounting, which is initiated skills training and professional skills in the area.